RNA m6A Modification Alteration by Black Phosphorus Quantum Dots Regulates Cell Ferroptosis: Implications for Nanotoxicological Assessment. Issue 3 (18th January 2021) - Ruan, Fengkai; Zeng, Jie; Yin, Hanying; Jiang, Shengwei; Cao, Xisen; Zheng, Naying; Han, Changshun; Zhang, Chuchu; Zuo, Zhenghong; He, Chengyong
Abstract: Nanosafety is a major concern for nanotechnology development. Evaluation of the transcriptome and the DNA methylome is proposed for nanosafety assessments. RNA m6A modification plays a crucial role in development, disease, and cell fate determination through regulating RNA stability and decay. Here, since black phosphorus quantum dots (BPQDs), among many other types of QDs, increase the global m6A level and decrease the demethylase ALKBH5 level in lung cells, the epitranscriptome is taken into consideration for the first time to evaluate nanosafety. Both the transcriptome and m6A epitranscriptome analyses show that BPQDs alter many biological processes, such as the response to selenium ions and the lipoxygenase pathway, indicating possible ferroptosis activation. The results further show that BPQDs cause lipid peroxidation, mitochondrial dysfunction, and iron overload. Recognition of these modified mRNAs by YTHDF2 leads to mRNAs' decay and eventually ferroptosis. This study shows that RNA m6A modification not only is a more sophisticated indicator for nanosafety assessment but also provides novel insight into the role of RNA m6A in regulating BPQD‐induced ferroptosis, which may be broadly applicable to understanding the functions of RNA m6A under stress. Abstract : RNA m6A methylations play an essential role in cell fates. Here, black phosphorus quantum dots (BPQDs) decrease the expression of demethylase ALKBH5 leading to the increase of global m6A level in lung cells. Transcriptome, m6A epitranscriptome, and following experiments further show that BPQDs cause lipid peroxidation, mitochondrial dysfunction, and iron overload. Mechanically, YTHDF2 recognizes the m6A on mRNAs resulting in ferroptosis.